A stigma-reduction intervention targeting abortion and contraceptive use among adolescents in Kisumu County, Kenya: a quasi-experimental study*. Issue 1 (31st December 2023) - Makenzius, Marlene; Rehnström Loi, Ulrika; Otieno, Beatrice; Oguttu, Monica
Abstract: This study assessed the effectiveness of a school-based stigma-reduction intervention focusing on stigmatising attitudes towards girls associated with abortion and contraceptive use. In February 2017, two gender-mixed secondary schools ( n  = 1368) in peri-urban areas of Kisumu County, Kenya, were assigned to receive either an 8-hour stigma-reduction intervention over four sessions (intervention school: IS) or standard comprehensive sexuality education (control school: CS). A classroom survey entailing two five-point Likert scales – the 18-item Adolescents Stigmatizing Attitudes, Beliefs and Actions (ASABA) scale, which measures abortion stigma, and the seven-item Contraceptive Use Stigma (CUS) scale – was conducted to collect data at baseline, 1-month and 12-months after the intervention. The intervention was to be considered effective if a mean score reduction of 25% was achieved for both the ASABA (primary outcome) and the CUS (secondary outcome) at the IS between baseline and 12-month follow-up. 1207 (IS = 574; CS = 633) students were included in analyses at 1-month follow-up, and 693 (IS = 323; CS = 370) at 12-months (the final-year students had left school). A decrease in mean score on both scales was observed at 1-month at both schools. At 12-months, the score decrease was 30.1% at the IS and 9.0% at the CS for ASABA, and 27.3% at the IS and 7.9% at the CS for CUS. At the IS, the score decrease for ASABA between baseline and 12-months was 23.3% among girls and 31.2% among boys; for CUS, the decrease was 27.3% and 24.3%, respectively. ASABA and CUS were positively correlated ( r  = 0.543; p  < 0.001), implying a broader perspective on reproductive stigma. A four-session, school-based stigma-reduction intervention could lead to transformed values and attitudes towards gender norms among adolescents regarding abortion and contraceptive use. Stigma associated with abortion and contraception should become a priority for high-quality CSE programmes.